Occasional detection of lupus erythematosus cells in bone marrow samples: A case report - Safaa Jassim Mohammed (Clinical Case Reports, 2021)
Abstract This unexpected observation in the smear indicated that an improved morphological analysis could provide a definitive guide for the detection of atypical SLE.